2011
DOI: 10.1371/journal.pone.0019003
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Mutagenesis of a Capsule-Like Complex (CLC) from Francisella tularensis, and Contribution of the CLC to F. tularensis Virulence in Mice

Abstract: Background Francisella tularensis is a category-A select agent and is responsible for tularemia in humans and animals. The surface components of F. tularensis that contribute to virulence are not well characterized. An electron-dense capsule has been postulated to be present around F. tularensis based primarily on electron microscopy, but this specific antigen has not been isolated or characterized.Methods and FindingsA capsule-like complex (CLC) was effectively extracted from the cell surface of an F. tularen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(120 citation statements)
references
References 61 publications
(87 reference statements)
7
113
0
Order By: Relevance
“…The previously described seven unique LPS genes were present in all the F. tularensis genomes but only sporadically present among the F. novicida genomes. Only the F. tularensis genomes contained all three genes previously mentioned (13,71,72) to be involved in the formation of a cell surface capsule-like structure; these genes were FTT0794 (phosphocholine metabolism), FTT0795 (formylmethyltransferase), and FTT0796 (phosphocholine metabolism) (13,73). The F. novicida U112 genome had only the OppABCDF locus and the four R-M systems identified previously (70).…”
Section: Resultsmentioning
confidence: 93%
“…The previously described seven unique LPS genes were present in all the F. tularensis genomes but only sporadically present among the F. novicida genomes. Only the F. tularensis genomes contained all three genes previously mentioned (13,71,72) to be involved in the formation of a cell surface capsule-like structure; these genes were FTT0794 (phosphocholine metabolism), FTT0795 (formylmethyltransferase), and FTT0796 (phosphocholine metabolism) (13,73). The F. novicida U112 genome had only the OppABCDF locus and the four R-M systems identified previously (70).…”
Section: Resultsmentioning
confidence: 93%
“…The strain was then extracted with 0.5% phenol as previously described (Bandara et al, 2011) and by a modified method using urea (Champion et al, 2015). Briefly, the bacteria were scraped off 10 agar plates and suspended in ~100 ml of 1 M urea.…”
Section: Methodsmentioning
confidence: 99%
“…Gels were stained with the Pierce Silver Stain Kit (Thermo Scientific), or 0.25% Stains-All (Sigma-Aldrich, St. Louis, MO; Bandara et al, 2011), or both.…”
Section: Methodsmentioning
confidence: 99%
“…This is important to note, since recent evidence has suggested that the O antigen and capsule of Francisella are structurally similar, with the capsule consisting of a polymer of O-antigen tetrasaccharide subunits (9) as well as a glycoprotein component termed a "capsulelike complex" (18). As such, some mutants deficient in LPS O-antigen production are also impaired in the production of capsule (9,130), including specific wbt operon mutants (wbtA, wbtC, wbtM, and wbtI).…”
Section: Complement and Antibodymentioning
confidence: 99%